Caracterização geotécnica e georreferenciamento de alguns depósitos de solos moles da região metropolitana de Aracaju - Sá, Letícia Menezes Santos (2019)
The good practice of Geotechnics Engineering requires an appropriate knowledge about the profile of subsoil layers where will be executed foundations and geotechnical works. Based on preliminary and complementary geotechnical investigations, it is possible to obtain information about these layers. However, it is common to find cases in which the negligence of subsoil investigations is observed. Thus, projects are elaborated without reliable geotechnical parameters, what leads to the appearance of problems and pathologies. These problems become harder when there is, in the subsoil, layers of highly compressible soils, which, in general, have low resistance and experienced high settlements by consolidation. Nowadays, there are still a few available data about geotechnical properties of soft soils presents in the subsoil of the Metropolitan Region of Aracaju. The present research is inserted in this context and has as the main purpose to evaluate the geotechnical properties of soft soil samples withdrawals from certain locals of the Metropolitan Region of Aracaju (MRA), based on field and laboratory tests. Thereby, it starts the formation of a data bank that can be used like reference for future studies and elaboration of geotechnical projects. Therefore, the characterization and georeferencing of eight soft soil deposits of the RMA were performed. The software QGIS 2.18.7 was used for the elaboration of maps containing relevant information about the geology, geomorphology and pedology of the georeferenced deposits. In addition, information about field (SPT and Vane test) and laboratory tests (characterization, consolidation, triaxial and simple compression), performed in the studied deposits, was entered in a database. It was verified that the RMA soft clay layers usually are intercalated with sandy layers, and that the percentage of clay of these deposits varies between 13% and 48%. As regards plasticity, the clayey soils of this region are classified as moderately plastics to very plastics (PI between 8 and 33). When compared to other Brazilian deposits, the soft soils of this study presented low moisture contents and predominance of inactive clays. Undrained shear strength values ranged from 2.5 to 19.0 kPa. The results obtained in this research are only the beginning of an investigation, characterization and cataloging process of the clayey soil deposits existing in the State of Sergipe, from which it is expected the development of new research aiming to broaden and refine the knowledge about these important geotechnical formations.